Recent Advances in Electrochemical Sensors and Biosensors for Detecting Bisphenol A - Somayeh Tajik; Hadi Beitollahi; Fariba Garkani Nejad; Kaiqiang Zhang; Quyet Van Le; Ho Won Jang; Soo Young Kim; Mohammadreza Shokouhimehr (Sensors, 2020)
In recent years, several studies have focused on environmental pollutants. Bisphenol A (BPA) is one prominent industrial raw material, and its extensive utilization and release into the environment constitute an environmental hazard. BPA is considered as to be an endocrine disruptor which mimics hormones, and has a direct relationship to the development and growth of animal and human reproductive systems. Moreover, intensive exposure to the compound is related to prostate and breast cancer, infertility, obesity, and diabetes. Hence, accurate and reliable determination techniques are crucial for preventing human exposure to BPA. Experts in the field have published general electrochemical procedures for detecting BPA. The present timely review critically evaluates diverse chemically modified electrodes using various substances that have been reported in numerous studies in the recent decade for use in electrochemical sensors and biosensors to detect BPA. Additionally, the essential contributions of these substances for the design of electrochemical sensors are presented. It has been predicted that chemically modified electrode-based sensing systems will be possible options for the monitoring of detrimental pollutants.